Correlation between component alignment and short-term clinical outcomes after total knee arthroplasty - Luan, Yichao; Zhang, Min; Ran, Tianfei; Wang, Huizhi; Fang, Chaohua; Nie, Maodan; Wang, Min; Cheng, Cheng-Kung (Frontiers in Surgery, 2022)
Objective: This study aimed to investigate the correlation between component alignment and short-term clinical outcomes after total knee arthroplasty (TKA). Methods: 50 TKA patients from a regional hospital were enrolled in the study. The following component alignments were measured from radiological data acquired within one week after surgery: hip-knee-ankle angle (HKA), medial distal femoral angle (MDFA), medial proximal tibial angle (MPTA), femoral flexion-extension angle (FEA), tibial slope angle (TSA), femoral rotational angle (FRA) and tibial rotational angle (TRA). The Hospital for Special Surgery (HSS) knee scoring system was used to assess clinical outcomes after one year, with patients being divided into three groups (excellent, good and not good) according to the HSS scores. Difference analysis and linear correlation analysis were used for the statistical analysis. Results: The results showed significant differences in MDFA (p=0.050) and FEA(p=0.001) among the three patient groups. It was also found that the total HSS had only a moderate correlation with FEA (r=0.572, p<0.001), but FEA had a positive linear correlation with pain scores (r=0.347, p=0.013), function scores (r=0.535, p=0.000), ROM scores (r=0.368, p=0.009), muscle scores (r=0.354, p=0.012) and stability scores (r=0.312, p=0.028). A larger MDFA was associated with lower FE deformity scores (r=-0.289, p=0.042) and the TSA had a positive influence on the ROM (r=0.436, p=0.002). Also, changes in FRA produced a consequent change in the FE deformity score (r=0.312, p=0.027), and the muscle strength scores increased as TRA increased (r=0.402, p=0.004). Conclusion: The results show that the FEA plays a significant role in clinical outcomes after TKA. Surgical techniques and tools may need to be improved to accurately adjust the FEA to improve joint functionality and patient satisfaction.